2016
DOI: 10.1007/s11999-015-4217-x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Hemarthroses After TKA Treated With an Intraarticular Injection of Yttrium-90

Abstract: Background Recurrent hemarthroses after a TKA are uncommon and usually respond to nonoperative treatment or intervention using angiographic embolization or synovectomy. However, in rare circumstances, the problem can be resistant to treatment. Case Description We report the case of a patient who had recurrent hemarthroses after a TKA. During the first 18 months after surgery, the patient experienced 48 episodes consistent with bleeding into the knee. The bleeding episodes recurred despite use of traditional tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Open surgical synovectomy has been reported to be successful in most cases but is associated with the complications and morbidity of repeated surgery such as loss of function and infection [1,2,4]. Radiosynovectomy is a promising technique; however, this is only documented in case reports [5]. Embolization of geniculate arteries has been reported in small series of patients and is considered a minimally invasive treatment with good clinical success and a low complication rate [3,6].…”
mentioning
confidence: 99%
“…Open surgical synovectomy has been reported to be successful in most cases but is associated with the complications and morbidity of repeated surgery such as loss of function and infection [1,2,4]. Radiosynovectomy is a promising technique; however, this is only documented in case reports [5]. Embolization of geniculate arteries has been reported in small series of patients and is considered a minimally invasive treatment with good clinical success and a low complication rate [3,6].…”
mentioning
confidence: 99%
“…In a case report by Kapetanos et al, the use of an intra-articular injection of yttrium-90 (Y-90) was effective in treating a recurrent hemarthrosis following total knee arthroplasty after conservative therapy and thermocoagulation failed 36 . Fine and Klestov replicated the successful use of synoviorthesis in a later case report, where Y-90 was successful in treating a refractory case of recurrent hemarthrosis that failed to respond to arthroscopic synovectomy as well as angiography 37 .…”
Section: Radiosynovectomy (Synoviorthesis)mentioning
confidence: 88%
“…Other single cases and case series reported recurrent hemarthrosis after TKA in patients with OA. [4][5][6][7][8][9] There were only two reports of recurrent hemarthrosis after TKA in patients with rheumatoid arthritis (RA). Ohdera et al 2 reported that recurrent hemarthrosis occurred in one (0.1%) of 625 RA patients after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Other single cases and case series reported recurrent hemarthrosis after TKA in patients with OA. 4 9 …”
Section: Introductionmentioning
confidence: 99%